Subthreshold Radiation Damage in Few-Layer Graphene Nanostructures Due to Low-Energy Electron Irradiation - Guseinov, N. R.; Ilyin, A. M. (New Approaches in Engineering Research Vol. 10, 2021)
Some preliminary results of experimental study (Raman spectroscopy, electron and optical microscopy, Auger spectroscopy) and theoretical discussion with computer modeling of few-layer graphene nanostructures, irradiated by SEM electron beams in the range 0.2 - 30 keV at room temperature with intensities varied in a wide interval on insulating (SiO2) and metallic (Ni foils) substrates are presented. The Raman spectroscopy data from irradiated specimens showed the obvious effect of substrate by all used beam energies. In the paper a new possible physical mechanism of subthreshold radiation structural damaging in a few-layer graphene and similar nanostructures is suggested.